Patterns of Alcohol Use and Daily Smoking Among Men Who Have Sex with Men in Nepal. - Paudel, Kiran; Gautam, Kamal; Hossain Sujan, Md Safaet; Adhikari, Prakash; Bhusal, Sandesh; Wickersham, Jeffrey A.; Bhakta, K. C.; Sapkota, Sabitri; Dhakal, Manisha; Adhikari, Tara Ballav; Shrestha, Roman (Journal of Community Health, 2025)
Men who have sex with men (MSM) have an elevated risk of adverse health outcomes associated with alcohol use and smoking. Although substantial studies have been conducted globally, little is known about alcohol use and smoking among MSM in Nepal. Therefore, the present study aimed to examine the prevalence and patterns of alcohol use and daily smoking among MSM in Nepal. A cross-sectional respondent-driven survey was conducted among MSM in Kathmandu, Nepal, between October and December 2022. Bivariate and multivariate logistic regression analyses were used to evaluate independent correlates of alcohol use in the past 12 months and daily smoking. Among 250 participants (mean age 27.6 ± 8.9 years), 71.6% had consumed alcohol in the past 12 months, and 42% smoked daily in the last 30 days. MSM who had an income of less than NRs 20,000 (aOR: 2.1; 95% CI: 1.1–3.8), were single (aOR: 2.0; 95% CI: 1.1–3.8), employed (aOR: 2.1; 95% CI: 1.1–4.1), engaged in sex work (aOR: 3.5; 95% CI: 1.1–11.1), ever smoked (aOR: 5.1; 95% CI: 2.6–9.7), and who did not engage in condomless sex (aOR: 2.1; 95% CI: 1.1–4.5) were more likely to use alcohol in the past 12 months. Similarly, participants who were born in Bagmati province (aOR: 3.7; 95% CI: 1.8–7.6), and had a history of drug use (aOR: 2.8; 95% CI: 1.3–5.7), and police detention (aOR: 3.2; 95% CI: 1.3–9.2) were more likely to be involved in daily smoking. The findings underscore the necessity of MSM-specific alcohol and smoking cessation programs in Nepal.